Fluxo de potência trifásico probabilístico para redes de distribuição usando o método de estimação por pontos - Gallego, Luis Alfonso [UNESP]; Echeverri, Mauricio Granada [UNESP]; Padilha-Feltrin, Antonio [UNESP] (FapUNIFESP (SciELO), 2012)
In this paper the point estimation method is applied to solve the probabilistic power flow problem for unbalanced three-phase distribution systems. Through the implementation of this method the probability distribution functions of voltages (magnitude and angle) as well as the active and reactive power flows in the branches of the distribution system are determined. Two different approaches of the point estimation method are presented (2m and 2m+1 point schemes). In order to test the proposed methodology, the IEEE 34 and 123 bus test systems are used. The results obtained with both schemes are compared with the ones obtained by a Monte Carlo Simulation (MCS).
Probabilistic three-phase power flow for distribution network using point estimate method
Keywords: Distribution system; Monte Carlo simulation; Point estimation method; Probabilistic power flow; Uncertainty; Distribution systems; Monte Carlo Simulation; Local area networks; Monte Carlo methods; Probability distributions; Estimation